Judiskt liv: en undersökning bland medlemmar i Stockholms Judiska Församling - Fischer, David (Megilla-Förl., 1996)
Zsfassung in engl. Sprache u.d.T.: Jewish life. A survey among the members of the Stockholm Jewish congregation